PAGPAPATAAS NG AKADEMIKONG PERPORMANS SA NASYONALISMO SA TIMOG KANLURANG ASYA GAMIT ANG SPOKEN POETRY SA ARALING PANLIPUNAN (World Bulletin of Social Sciences, 2021)
Teaching the history of nationalism in West Asia requires strategies that will arouse the interest, skill, and learning of students. The main objective of this study is to increase the academic performance of students in learning the concept of nationalism in Southwest Asia using Spoken Poetry in Social Studies. The participants in this research were the two groups from grade 7 of a national high school with the lowest mastery level in the said subject. One group was assigned as members of the experimental group while the other section served as members of the control group. The pretest scores obtained by the two groups showed that both groups had limited knowledge about the topic of Nationalism in Southwest Asia. After several days of discussing the topic using the Spoken Poetry strategy, the posttest was conducted and the experimental group obtained 19.56 mean score, while the Control group obtained 11.64 mean score. The mean gain of 7.92 was favorable to the members of the experimental group. Thus, significant increase in the level of performance of the students was evident as computed t-value of 9.53 was higher than the critical value of 4.83. Also, results of the focus group discussion revealed that the students have became more interested, engaged, and learned better in the given topic. Therefore, the nully hypothesis was rejected. This means that there was a significant difference between the performances of the students taught using spoken word poetry and those facilitated using conventional teaching strategy. Hence, the researchers recommended that the students should have a longer preparation time in producing spoken poetry pieces.